2023
DOI: 10.1108/ijotb-08-2022-0159
|View full text |Cite
|
Sign up to set email alerts
|

Organizational career development and retention of millennial employees: role of job satisfaction, organizational engagement and employee empowerment

Abstract: PurposeThe study aims to examine the relationship between organizational career development (OCD) and employee retention (ER) with job satisfaction (JS) and organizational engagement as the mediating variables and employee empowerment (EE) as moderating variable between the relationship of OCD and JS.Design/methodology/approachA total of 422 respondents – employees working in information technology (IT) company in India – were collected and subjected to analysis through structural equation modelling (SEM).Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…These results align with Mahmood et al (2019) who found that salary is a significant factor influencing employee satisfaction. Similar to compensation, career development programs have been shown to positively impact employee job satisfaction (Jena & Nayak, 2023;Permana et al 2021). This study aligns with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…These results align with Mahmood et al (2019) who found that salary is a significant factor influencing employee satisfaction. Similar to compensation, career development programs have been shown to positively impact employee job satisfaction (Jena & Nayak, 2023;Permana et al 2021). This study aligns with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…The third aspect is the effect of career development towards work satisfaction. Career development was defined as helping an employee be the best individual they can be in the organization and finding the right place for them,but not just about promotion [9]. It can be seen that career development emphasize on the degree of matching between individual employee's ability and position as well as the enhancement of individual employee's skills and qualities.…”
Section: Career Developmentmentioning
confidence: 99%
“…They prefer challenging jobs that provide a sense of significance and enthusiasm however, they are criticized for losing the job value easily (Brown et al, 2015;Hurtienne et al, 2022;Naim and Lenka, 2018). Moreover, Gen Y employees will constitute the major proportion of the hospitality workforce in the future, and thus, there is a dire need for specific HR practices to enhance their engagement (Baum, 2019;Huertas-Valdivia et al, 2018;Jung et al, 2021;Jena and Nayak, 2023). Gen Y shows greater desire for supportive management, continuous development, and work-life balance in hospitality (Hamouche et al, 2023;He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Third, it broadens the study of EE to the hospitality and tourism industry in developing countries such as India, where the norm of reciprocation may differ from that of industrialized countries. Moreover, Gen Y employees account for around 25% of the global population and approximately 50% of the overall Indian population, and they are characterized by frequent job changes (Jena and Nayak, 2023).…”
Section: Introductionmentioning
confidence: 99%